2018
DOI: 10.1002/ajmg.b.32641
|View full text |Cite
|
Sign up to set email alerts
|

Is BDNF‐Val66Met polymorphism associated with psychotic experiences and psychotic disorder outcome? Evidence from a 6 years prospective population‐based cohort study

Abstract: There is little research on genetic risk for the extended psychosis phenotype ranging from psychotic experiences (PEs) to psychotic disorders (PDs). In this general population-based prospective cohort study, the longitudinal associations between BDNF-Val66Met polymorphism and the different levels of the extended psychosis phenotype were investigated. Addresses were contacted in a multistage clustered probability sampling frame covering 11 districts and 302 neighborhoods at baseline (n = 4011). A nested case-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Previous studies have indicated that the Val66Met polymorphism of BDNF gene might play an important role in the pathophysiology of several psychotic disorders (Gattere et al 2018, Kirli et al 2018, Rybakowski 2008. The association between Val66Met and OCD susceptibility has been widely studied, although inconsistent results were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the Val66Met polymorphism of BDNF gene might play an important role in the pathophysiology of several psychotic disorders (Gattere et al 2018, Kirli et al 2018, Rybakowski 2008. The association between Val66Met and OCD susceptibility has been widely studied, although inconsistent results were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The primary diagnosis of participants encompasses schizophrenia and schizophrenia spectrum disorders, as well as other psychotic spectrum disorders as a subcategory for comparison – as in Karacetin ( 38 ). Kirli ( 29 ) studied individuals with psychotic experiences and psychotic disorders, including schizophrenia, to investigate longitudinal associations between the BDNF Val66Met polymorphism and different levels of the extended phenotype. Another study compared genotyping differences between healthy volunteers and unaffected first-degree relatives of patients with schizophrenia ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies included a healthy control group, except those looking for associations between the BDNF Val66Met polymorphism and clinical facets of schizophrenia or the extended psychosis phenotype ( 29 , 36 ), or evaluating genetic implications in treatment resistance ( 30 ).…”
Section: Discussionmentioning
confidence: 99%